OPTIMALISASI PENGALOKASIAN PUPUK DI PTPN XIII KELAPA SAWIT AFDELING IV LABURAN KABUPATEN PASER - Adi Suroso, Annisa Rahmani Putri, LCA. Robin Jonatha (EKONOMIA, 2015)
Formulation the problem in this research is does the allocation of fertilizer made by PTPN XIII Palm Oil Afdeling IV Laburan District Paser is optimal.Â A purpose of the objectives in this study were: 1) To know and analyze the allocation of fertilizer made by PTPN XIII Palm Oil Afdeling IV Laburan District Paser, 2) To obtain a low cost fertilizer allocation (minimal).The analytical tool used is a transportation method beginning solution with the Least Cost in advance to allocation fertilizer from the smallest allocate cost and a Stepping Stone to final solution by evaluating the results obtained from beginning solution making change of cost allocation is negative.Based on the analysis and discussion it can be concluded, results of calculation of the total allocation cost of use fertilizer by companies when compared with results total allocation cost of fertilizers using Least Cost method which was evaluated by Stepping Stone method then are considerable difference. This thing show the fertiliz1er allocation made by PTPN XIII Palm Oil Afdeling IV Laburan District Paser not optimal. Thus the hypothesis proposed received in this study.